ON THE NEED TO RESEARCH AND STUDY THE POETRY OF S. ERALIEV FROM A LINGUISTIC POINT OF VIEW (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Linguistic analysis of S. Eraliev’s poetry opens the way to a deep understanding of the poetic capabilities of the Kyrgyz language through the study of its vocabulary, syntax, metaphors and stylistic features.
Keywords: semantic-stylistic layer, genre of poetry, artistic means of speech, research, artistic language, poetic skill, stylistic layers, syntactic structure.